Telemodernities Television and Transforming Lives in Asia - Lewis, Tania; Martin, Fran; Sun, Wanning (Duke University Press, 2016)
Yoga gurus on lifestyle cable channels targeting time-pressured Indian urbanites; Chinese dating shows promoting competitive individualism; Taiwanese domestic makeover formats combining feng shui with life planning advice: Asian TV screens are increasingly home to a wild proliferation of popular factual programs providing lifestyle guidance to viewers. In Telemodernities Tania Lewis, Fran Martin, and Wanning Sun demonstrate how lifestyle-oriented popular factual television illuminates key aspects of late modernities in South and East Asia, offering insights not only into early twenty-first-century media cultures but also into wider developments in the nature of public and private life, identity, citizenship, and social engagement. Drawing on extensive interviews with television industry professionals and audiences across China, India, Taiwan, and Singapore, Telemodernities uses popular lifestyle television as a tool to help us understand emergent forms of identity, sociality, and capitalist modernity in Asia
Description based on online resource; title from PDF title page (publisher's Web site, viewed 25. Nov 2020)
Keywords: PERFORMING ARTS / Television / History & Criticism; Reality television programs -- China; Reality television programs -- India; Reality television programs -- Taiwan